Analysis of The Ability to Solve Mathematical Problems in Solving Pythagorean Theorem - Muhammad Farhan Fadillah; Ainna Anggriani Pohan; Laila Dytul Husna; Yulia Lestari; Dwi Novita Sari (Riemann: Research of Mathematics and Mathematics Education, 2024)
The purpose of this study was to test students' ability to solve mathematical problems using Pythagorean theorem material. The subjects of this study were grade VIII students of SMP Ani Idrus perguruan ERIA, a class consisting of twenty children selected using purposive sampling techniques, where six students were selected based on their ability to the instruments in this study, along with supporting instruments such as test instruments for students' mathematical problem-solving abilities and interview procedures. The findings showed that while students in the high-ability category were able to solve problems, they lacked comprehensiveness in reading questions. Advanced students cannot solve a given problem because they can only understand it. Students who are classified as poor in ability are no longer able to answer the challenges given because they continue to struggle to understand the questions given.